Unraveling Investor Behavior: Exploring the Influence of Behavioral Finance on Investment Decision-Making - Chauhan, Rahul; Patel, Neerav (Indonesian Journal Publisher, 2024)
The primary objective of this study is to gain a comprehensive understanding of how behavioral biases and psychological factors impact investment choices in a real-world context, with a specific focus on Baroda City. By analyzing awareness, innovation, purchasing power, online purchasing, and internet usage, the research aims to offer insights into the motivations and challenges faced by investors. A sample of 98 respondents is selected, and data is collected through surveys and interviews. The survey questionnaire assesses various behavioral finance factors, including the awareness of investment opportunities, innovative financial instruments, purchasing power, online investment behavior, and internet usage. Smart PLS is utilized for structural equation modeling and path analysis, while SPSS is employed for descriptive and inferential statistical analysis. The collected data undergoes thorough analysis to uncover the relationships between awareness, innovation, purchasing power, online investment behavior, and internet usage, and their impact on investment decisions. Smart PLS aids in examining structural relationships, and SPSS is instrumental in conducting statistical tests to validate the research hypotheses. The study reveals valuable insights into how behavioral biases and psychological factors shape investment decisions. It provides an understanding of the significance of awareness, innovation, purchasing power, online investment behavior, and internet usage in influencing investment choices and risk-taking behavior. The research findings indicate that awareness of investment opportunities and innovative financial instruments significantly affect investment decisions. Purchasing power emerges as a crucial determinant, and online investment behavior and internet usage exhibit positive relationships with investment choices in Baroda City. The study acknowledges certain limitations, including the sample size and geographical scope, which may restrict the generalizability of the findings. Additionally, behavioral finance is a complex field, and the study may not encompass all possible behavioral biases and psychological factors affecting investment decisions.